Transdentinal cytotoxicity of carbodiimide (EDC) and glutaraldehyde on odontoblast-like cells - Scheffel, Débora Lopes Salles [UNESP]; Bianchi, Luciana [UNESP]; Soares, Diana Gabriela [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Sabatini, Camila [UNESP]; Souza Costa, Carlos Alberto de [UNESP]; Pashley, David H.; Hebling, Josimeri [UNESP] (Operative Dentistry, 2015)
Objective: To evaluate the transdentinal cytotoxicity of three different concentrations of carbodiimide (EDC) or 5% glutaraldehyde (GA) on MDPC-23 cells. Methods: Seventy 0.4-mm-thick dentin disks obtained from human molars were adapted to artificial pulp chambers. MDPC-23 cells were seeded on the pulpal surface of the disks. After 48 hours, the occlusal dentin was acid-etched and treated for 60 seconds with one of the following solutions (n=10): no treatment (negative control); 0.1 M, 0.3 M, or 0.5 M EDC; 5% GA; Sorensen buffer; or 29% hydrogen peroxide (positive control). Cell viability and morphology were assessed by methyltetrazolium assay and scanning electron microscopy (SEM), respectively. The eluates were collected after the treatments and applied on MDPC-23 seeded in a 24-well plate to analyze cell death, total protein (TP), and collagen production. The last two tests were performed 24 hours and seven days after the challenge. Data were analyzed by Kruskal-Wallis and Mann-Whitney tests (p<0.05). Results: EDC at all test concentrations did not reduce cell viability, while 5% GA did increase cell metabolism. Cell death by necrosis was not elicited by EDC or 5% GA. At the 24-hour period, 0.3 M and 0.5 M EDC reduced TP production by 18% and 36.8%, respectively. At seven days, increased TP production was observed in all groups. Collagen production at the 24-hour period was reduced when 0.5 M EDC was used. After seven days, no difference was observed among the groups. SEM showed no alteration in cell morphology or number, except in the hydrogen peroxide group. Conclusions: Treatment of acid-etched dentin with EDC or GA did not cause transdentinal cytotoxic effects on odontoblast-like cells.
Keywords: Glutaraldehyde; Carbodiimide; Cytotoxicity; Odontoblast-like cell; Dentin